2018
DOI: 10.1007/s00348-018-2580-6
|View full text |Cite
|
Sign up to set email alerts
|

Bichromatic synthetic schlieren applied to surface wave measurements

Abstract: The present paper provides an introduction to Bichromatic Synthetic Schlieren (BiCSS) for surface measurements, a novel extension of the Free Surface Synthetic Schlieren (FS-SS) by Moisy et al. (2009). The new technique is based on the fact that light diffraction through a medium varies with wavelength. Therefore, one may apply light at two different wavelengths to measure the change in density gradient in a medium. This paper explores the use of the difference between blue visual and near-infrared (NIR) light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The projection of many patterns could also allow to project patterns with multiple characteristics (e.g., dot size) and chose, a posteriori, the best one or even a combination of patterns. The measurements are taken at t = 0 T, 5 T, 250 T , and 500 T Digital projectors also allow for the projection of colored patterns, which were not discussed here, but Kolaas et al (2018) showed that monochromatic light can improve the measurements of a water surface since light diffraction is wavelength dependent. In our first experimental configuration, no significant difference was observed in terms accuracy in preliminary experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The projection of many patterns could also allow to project patterns with multiple characteristics (e.g., dot size) and chose, a posteriori, the best one or even a combination of patterns. The measurements are taken at t = 0 T, 5 T, 250 T , and 500 T Digital projectors also allow for the projection of colored patterns, which were not discussed here, but Kolaas et al (2018) showed that monochromatic light can improve the measurements of a water surface since light diffraction is wavelength dependent. In our first experimental configuration, no significant difference was observed in terms accuracy in preliminary experiments.…”
Section: Discussionmentioning
confidence: 99%
“…A much older technique that can be classified as space-time is direct optical imaging of the surface, which is based on the lens effect from the wave crests and troughs on the light crossing the rippled surface [9,59]; this option allows 3D reconstruction under the condition that the surface shape has flat or radial symmetry, which is fulfilled for the ripples normally investigated with capillary waves apparatuses. Moisy et al [60] reconstructed the surface topography of gravitational-capillary waves (~10 Hz) using free-surface synthetic Schlieren technique (distortion of a printed pattern by refraction from the deformed liquid surface); a number of variants of this technique exist [48,49,61,62,63] and Vinnichenko et al [44] used reflection rather than refraction. The variants of the Schlieren imaging are somewhat limited in space resolution and are more suited to study gravity-capillary waves than shorter capillary waves.…”
Section: Techniques To Detect Wavesmentioning
confidence: 99%
“…More details on global least-squares reconstruction and further advanced methods can be found in the works by Harker and O'Leary (2008), Harker and O'Leary (2011) and Harker and O'Leary (2015). We use the implementation by D'Errico which is now commonly used in reconstruction problems that involve an inverse gradient operation to be performed on a mesh of spatial gradients (Moisy et al 2009;Simonini et al 2021;Kolaas et al 2018;Kaufmann et al 2020). An example of the reconstructed surface profile, based on the typical displacement field shown in Fig.…”
Section: Inverse Gradient Operationmentioning
confidence: 99%